EVALUASI PENERAPAN BAJA TULANGAN BETON DI INDONESIA - Biatna Dulbert Tampubolon; Erniningsih Erniningsih; Heru Suseno (Badan Standardisasi Nasional, 2007)
Planning of technical regulation must be done taken carefully to avoid incidence of negative impact for growth of climate is effort and the healthy emulation. There is indication in market a lot circulating product become militant bone of concrete disagree with standard.From survey of field as a whole mount accomplishment of sample become militant bone of concrete to conditions of SNI 07-2052-2002 still be very low (1,8%) so that need correction of denoting of standard, technical regulation and its mechanism, observation of pre-market and market and distribution